In vitro analysis of thimerosal genotoxicity and cytotoxicity effect - Mačkić-Đurović, Mirela; Dzenana Klepo,; Aščerić, Amina; Rukavina, Dunja; Aganović-Mušinović, Izeta (Asian Journal of Medical Sciences, 2023)
Background: Thimerosal is an organomercury compound with high mercury content. Thimerosal is located in the market as an effective bacteriostatic in a series of pharmaceutical products, ophthalmic and nasal products, immunoglobulin preparations, and as a preservative in vaccines. Aims and Objectives: Since it is a compound with living content, this study aimed to examine the genotoxic and cytotoxic potential of thimerosal in human lymphocytes culture. Materials and Methods: We used chromosome aberration analysis and cytokinesis-block micronucleus cytome (CBMN-Cyt) assay to test its genotoxic and cytotoxic potential in human lymphocyte culture. Results: Results showed that the frequency of structural chromosome aberrations and CBMN-cyt assay was significantly increased in treated cultures (1 μg/ml and 0.5 μg/ml) compared to the negative control. Conclusion: Obtained results and statistical analysis show that thimerosal is genotoxic and cytotoxic in human lymphocytes in tested concentrations.